2009
DOI: 10.1258/td.2009.080373
|View full text |Cite
|
Sign up to set email alerts
|

The incidence, clustering and characteristics of Burkitt lymphoma in the Northwest province of Cameroon

Abstract: The epidemiology of Burkitt lymphoma (BL) has never been documented in Cameroon. Data were collected from 16 hospitals, the Delegation of Public Health and the regional pathologist in the Northwest province of Cameroon on all BL cases. The incidence of BL in this region is 5.9/100,000 children aged <15 years/year - the second highest incidence documented to date. Significant clustering was also identified in Ndop, a low-lying region with a high malaria endemicity, at 21.5 cases/100,000 children aged <15 year/y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…Significant clustering was identified in the province, with a small, low-lying district found to have an incidence of 21.5/100,000. 1 Within the lymphoma belt, the highest documented incidence of BL was in Ibadan, Nigeria and was 8.4/ 100,000 children ,15 years of age per year (1960)(1961)(1962)(1963)(1964)(1965)(1966). 2 Brubaker et al 3 found an incidence of 5.7/100,000 in Tanzania (1964Tanzania ( -1970, Wabinga et al 4 found an incidence of 4.3/100,000 in Uganda (1963)(1964)(1965)(1966)(1967)(1968)) and Rainey et al 5 found an incidence of 2.15/100,000 in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…Significant clustering was identified in the province, with a small, low-lying district found to have an incidence of 21.5/100,000. 1 Within the lymphoma belt, the highest documented incidence of BL was in Ibadan, Nigeria and was 8.4/ 100,000 children ,15 years of age per year (1960)(1961)(1962)(1963)(1964)(1965)(1966). 2 Brubaker et al 3 found an incidence of 5.7/100,000 in Tanzania (1964Tanzania ( -1970, Wabinga et al 4 found an incidence of 4.3/100,000 in Uganda (1963)(1964)(1965)(1966)(1967)(1968)) and Rainey et al 5 found an incidence of 2.15/100,000 in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiology of BL shows that the endemic type is mainly confined to equatorial Africa and has a close association with EBV and malaria. Cameroon is a SSA country in the eBL belt and recent evidence shows that the incidence of BL in the North-West region of the country is the second highest in Africa and one of the highest documented worldwide (5.9/100,000) [ 6 ]. Studies have shown that constraints on establishing a complete diagnosis and staging, frequency of advanced disease at presentation and high drop-out rates during treatment makes for poorer prognosis [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above relationship has been found in nearly all cases as compared to only 20-30% in the sporadic cases [ 4 ] and about 35% in the immunodeficiency-related variant [ 5 ]. Its incidence is high among children less than 15 years of age, with special predilection for the abdomen (78%) and head and neck (62%) or both (42%) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of CHIKV activity were documented around the time when space-time case clusters of eBL were occurring in Malawi [105], and there was a statistically significant association between recent infection with that virus and the onset of eBL [12, 22]. High levels of CHIKV activity were also recorded in NW Cameroon [203] around the time when extremely high rates of eBL were recorded, up to 20/100,000, and spatial clusters were observed [100]. Although no analysis for space-time clustering was performed in Cameroon, it is likely that this was occurring, particularly in one area where the spatial clustering was very pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Endemic BL exhibits unusual features such as seasonality [95, 96], shifting foci, or lymphoma “hot-spots” which change location from year to year [97, 98] and both spatial [99, 100] and space-time case clusters [95, 97, 98, 101–104]. The clustering was very striking when it occured; in the Aliba outbreak, four of the five cases from this small village presented within one year [101] and unrelated cases in clusters in Malawi were often very close in space and time, with one unrelated case-pair living in neighbouring huts.…”
Section: Burkitt's Lymphomamentioning
confidence: 99%